Level of athlete satisfaction and group cohesion in adult indoor soccer teams - José Roberto Andrade do Nascimento Junior; Lenamar Fiorese Vieira; Eberton Alves de Souza; José Luiz Lopes Vieira (Universidade Federal de Santa Catarina, 2011)
This descriptive study investigated the levels of athlete satisfaction and group cohesion in adult indoor soccer teams. Fifty-eight male athletes of the Parana indoor soccer. Championship participated in the study. The Athlete Satisfaction Questionnaire and the Group Environment Questionnaire were used for assessment. The Kolmogorov-Smirnov test, Cronbach's alpha, Spearman's correlation coefficient, Manova, and the post hoc Scheffe test were used for data analysis (p < 0.05). The results showed that teams with higher levels of athlete satisfaction had higher perception of group cohesion. Teams with low levels of personal satisfaction had lower perception of group cohesion. Comparison of the teams showed differences in three dimensions of satisfaction (training-education, team performance, and strategy) and in all dimensions of cohesion. The more satisfied the athletes were with the instruction of the coach, personal treatment and strategies, the more cohesive were the teams for the task. It was concluded that the level of athlete satisfaction plays a key role in the perception of cohesion in sport teams, with a predominance of aspects related to the group-task dimensions over social-group dimensions.